Unhomely Experiences and Cultural Integration in Umm Zakiyyah’s Muslim Girl - Nur Asiyah; Muh Arif Rokhman; Lilik Istiqomah; Hidayatul Nurjanah; Nafila Azzahra (UIN Syarif Hidayatullah Jakarta, 2026)
This study investigates how unhomely experiences shape the process of cultural adaptation and identity negotiation in Umm Zakiyyah's Muslim Girl., focusing on the protagonist, Inaya, a Muslim girl who moves from Saudi to America. This study examines how Inaya’s unhomely experiences lead her to negotiate identity and develop strategies for cultural integration. Employing a descriptive qualitative approach, this study analyzes textual data drawn from the novel. Two theories are used in this research: the first, Homi Bhabha's concept of the unhomely, which reveals how Inaya feels alienated in society; and the second, John W. Berry's acculturation theory, which explains how the prominent figure accepts and adapts to the new culture through integration. The findings reveal that Inaya’s unhomely experiences manifest as awkwardness, uncanniness, incoherence, and instability. These conditions are shaped by cultural differences, religious visibility, and social interaction in the host society. However, these experiences do not remain unresolved. Inaya gradually develops coping strategies through school participation, social recognition, and identity negotiation, which lead her toward cultural integration. With several experiences, Inaya's growth has involved being an open minded, adapting to new environments, participating in social events, achieving academically, and respecting others. This research demonstrates that unhomely experiences transform into an integrated identity through the negotiation of a hybrid identity while maintaining her religious faith. Thus, this research contributes to diaspora studies, Muslim identities, and modern intercultural communication.